Korrika, running in collective effervescence through the Basque Country: A model of collective processes and their positive psychological effects - Zabala, Jon; Conejero, Susana; Pascual, Aitziber; Zumeta, Larraitz N.; Pizarro, José J.; Alonso-Arbiol, Itziar (Frontiers in Psychology, 2023)
The neo-Durkheimnian model suggests that feedback and emotional communion between participants during a collective gathering (i.e., perceived emotional synchrony: PES) is one of the key mechanisms of collective processes. This shared emotional experience gives rise, in turn, to more intense emotions, this being one of the explanatory models of the positive psychological effects of collective participation. Through a quasi-longitudinal design of three measurement-times (N = 273, 65.9% women; age: 18–70, M = 39.43, SD = 11.64), the most massive social mobilization that is celebrated in favor of the Basque language in the Basque Country (Korrika) was analyzed. Repeated measures and sequential mediation analyzes supported the model. The effect of participation on social integration was mediated by the increase in emotions of enjoyment through PES; the effect on social acceptance, social contribution, and social actualization was mediated by increased kama muta through PES; the effect on collective empowerment was mediated by the increase in self-transcendent emotions through PES; and the effect on remembered well-being was partially mediated by PES. Finally, it was also verified for the first time that the effect of participation on social integration, social acceptance and social actualization was maintained through PES (but not through emotions) for at least 6–7 weeks after the event ended. Also, it is concluded that Kama muta is a relevant emotion during collective gatherings.